Leakage Via Aberrant Bile Duct Due to Cholangiocarcinoma. Issue 2 (1998) - Stanton, R.; Craig, P. I.; Jorgensen, J. O.; Morris, D. L.
Abstract : The case of a male who had an open cholecystectomy complicated by presistent bile leak from an aberrant bile duct is presented. The persistence and volume of bile leak resulted in subsequent investigation of the biliary tree which demonstrated a cholangiocarcinoma of the right hepatic duct. This case is presented as an unusual presentation of cholangiocarcinoma and to highlight the value of modern techniques in imaging the biliary tree.